(untitled) (Annals of Medical Research, 2021)
Aim: Laparoscopic approach for complicated appendicitis (CA) is a controversial issue. Although it has been generally recommended, conflicting results have been reported in literature. The aim of this study is to obtain the current results regarding laparoscopic surgery for CA.